ATF3 -activated accelerating effect of LINC00941/lncIAPF on fibroblast-to-myofibroblast differentiation by blocking autophagy depending on ELAVL1/HuR in pulmonary fibrosis. Issue 11 (2nd November 2022) - Zhang, Jinjin; Wang, Haixia; Chen, Hongbin; Li, Hongbo; Xu, Pan; Liu, Bo; Zhang, Qian; Lv, Changjun; Song, Xiaodong
ABSTRACT: Idiopathic pulmonary fibrosis (IPF) is characterized by lung scarring and has no effective treatment. Fibroblast-to-myofibroblast differentiation and myofibroblast proliferation and migration are major clinical manifestations of this disease; hence, blocking these processes is a practical treatment strategy. Here, highly upregulated LINC00941/lncIAPF was found to accelerate pulmonary fibrosis by promoting fibroblast-to-myofibroblast differentiation and myofibroblast proliferation and migration. Assay for transposase-accessible chromatin using sequencing and chromatin immunoprecipitation experiments elucidated that histone 3 lysine 27 acetylation (H3K27ac) activated the chromosome region opening in the LINC00941 promoter. As a consequence, the transcription factor ATF3 (activating transcription factor 3) bound to this region, and LINC00941 transcription was enhanced. RNA affinity isolation, RNA immunoprecipitation (RIP), RNase-RIP, half-life analysis, and ubiquitination experiments unveiled that LINC00941 formed a RNA-protein complex with ELAVL1/HuR (ELAV like RNA binding protein 1) to exert its pro-fibrotic function. Dual-fluorescence mRFP-GFP-MAP1LC3/LC3 (microtubule associated protein 1 light chain 3) adenovirus monitoring technology, human autophagy RT 2 profiler PCR array, and autophagic flux revealed that the LINC00941 -ELAVL1 axis inhibited autophagosome fusion with a lysosome. ELAVL1 RIP-seq, RIP-PCR, mRNA stability, and rescue experiments showed that the LINC00941 -ELAVL1 complex inhibited autophagy by controlling the stability of the target genes EZH2 (enhancer of zeste 2 polycomb repressive complex 2 subunit), STAT1 (signal transducer and activators of transcription 1) and FOXK1 (forkhead box K1). Finally, the therapeutic effect of LINC00941 was confirmed in a mouse model and patients with IPF. This work provides a therapeutic target and a new effective therapeutic strategy related to autophagy for IPF. Abbreviations: ACTA2/a-SMA: actin alpha 2, smooth muscle; ATF3: activating transcription factor 3; ATG: autophagy related; Baf-A1: bafilomycin A1 ; BLM: bleomycin; CDKN: cyclin dependent kinase inhibitor; CLN3: CLN3 lysosomal/endosomal transmembrane protein, battenin; COL1A: collagen type I alpha; COL3A: collagen type III alpha; CXCR4: C-X-C motif chemokine receptor 4; DRAM2: DNA damage regulated autophagy modulator 2; ELAVL1/HuR: ELAV like RNA binding protein 1; EZH2: enhancer of zeste 2 polycomb repressive complex 2 subunit; FADD: Fas associated via death domain; FAP/FAPα: fibroblast activation protein alpha; FOXK1: forkhead box K1; FVC: forced vital capacity; GABARAP: GABA type A receptor-associated protein; GABARAPL2: GABA type A receptor associated protein like 2; IGF1: insulin like growth factor 1; IPF: idiopathic pulmonary fibrosis; LAMP: lysosomal associated membrane protein; lncRNA: long noncoding RNA; MAP1LC3/LC3: microtubule associated protein 1 light chain 3; NPC1: NPC intracellular cholesterol transporter 1; RGS: regulator of G protein signaling; RPLP0: ribosomal protein lateral stalk subunit P0; ROC: receiver operating characteristic; S100A4: S100 calcium binding protein A4; SQSTM1/p62: sequestosome 1; STAT1: signal transducers and activators of transcription 1; TGFB1/TGF-β1: transforming growth factor beta 1; TNF: tumor necrosis factor; UIP: usual interstitial pneumonia; ULK1: unc-51 like autophagy activating kinase 1; VIM: vimentin.